There but for the - Smith, Ali, 1962- (Pantheon Books, 2011)
At a dinner party in the posh London suburb of Greenwich, Miles Garth suddenly leaves the table midway through the meal, locks himself in an upstairs room, and refuses to leave. An eclectic group of neighbors and friends slowly gathers around the house, and Miles's story is told from the points of view of four of them: Anna, a woman in her forties; Mark, a man in his sixties; May, a woman in her eighties; and a ten-year-old named Brooke. The thing is, none of these people knows Miles more than slightly. How much is it possible for us to know about a stranger? And what are the consequences of even the most casual, fleeting moments we share every day with one another?